Toxicities Associated With PD-1/PD-L1 Blockade. Issue 1 (January 2018) - Wang, Daniel Y.; Johnson, Douglas B.; Davis, Elizabeth J.
Abstract : Abstract: Immune checkpoint inhibitors, particularly those targeting PD-1/PD-L1, produce durable responses in a subset of patients across cancer types. Although often well tolerated, these agents can induce a broad spectrum of autoimmune-like complications that may affect any organ system. Treatment of these toxicities primarily consists of immune suppression with corticosteroids and other agents. This review briefly discusses the mechanisms of immune-related adverse events, overviews the clinical and pathologic features of major toxicities caused by PD-1/PD-L1 blockade, and reviews their management.